Association of Meibomian Gland Dysfunction with Serum Lipid Profile: A Hospital-based Cross-sectional study - Shakya, Prasansa; Parajuli, Sanket; Sharma, Sadhana (Nepalese Journal of Ophthalmology, 2023)
Introduction: Meibomian gland dysfunction (MGD) frequently leads to ocular surface disease, yet its impact on patients’ overall health is often overlooked. With increase in sedentary lifestyle, decreased physical activities and exposure to the digital world people have been facing increasing incidence of dyslipidemia. Objectives: To investigate the association between serum lipid profile with severity of meibomian gland dysfunction. Materials and methods: This was an observational, analytical, cross-sectional study carried out in the department of Ophthalmology of Shree Birendra hospital from January 2019 to January 2020. Oxford grading scale was used to grade the severity of MGD as none (grade 0), mild (grade I and II), moderate (grade III), and severe (grade IV and V). Serum lipid profile was obtained from all patients with MGD and analysis was carried out. Results: Among 100 patients in this study majority of the participants were from the age group 61-70 (n, 40%) among whom 54 (54%) were females and 46 (46%) were males. Statistically significant association was noted between increase in total cholesterol, LDL, and TG levels with severity of MGD. However no significant association was found between HDL and the stage of MGD. Conclusion: This study demonstrated that patients with increasing severity of meibomian gland dysfunction had greater abnormalities in their serum lipid profiles with respect to total cholesterol, LDL and triglycerides